Influence of the direction of rotation on the wake characteristics of closely spaced counter-rotating vertical-axis wind turbines. Issue 6 (September 2020) - Vergaerde, Antoine; Troyer, Tim De; Muggiasca, Sara; Bayati, Ilmas; Belloli, Marco; Runacres, Mark C.
Abstract: Closely spaced counter-rotating vertical-axis wind turbines (VAWTs) exhibit a considerable power improvement compared to the same turbines in isolation. It thus makes sense to study their potential for wind farm production optimisation. With this objective in mind, the wake of an isolated VAWT is compared experimentally to the wake of counter-rotating VAWTs. Because of the unsteady aerodynamics, the wake of an isolated VAWT deflects towards the region behind its upwind moving blade. The direction of rotation thus directly influences the deflection of the wake. For paired configurations, it is possible to use this wake deflection as an advantage. A pair of counter-rotating VAWTs where the upwind moving blades are at the centre of the pair, exhibits a particularly narrow wake. With the benefit of a power improvement and a narrow wake, closely spaced counter-rotating VAWTs exhibit promising characteristics to improve the power density in a wind farm.